2010
DOI: 10.1007/s11663-009-9336-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Aggregates on the Properties of Carbon Refractories for a Blast Furnace

Abstract: The effect of carbon aggregates on the carbon refractory properties for a blast furnace was studied with X-ray diffraction (XRD), scanning electron microscopy (SEM), an energydispersive X-ray, mercury porosimetry, a resistivity instrument, and a laser thermal conductivity meter. The results showed that the microporous structure of a sample was determined by the amount of b-SiC whiskers. The thermal conductivity was controlled by the thermal conductivity of the corresponding carbon aggregate, and the alkali and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…For example, in blast furnace molten metal could easily penetrate into pores of carbon blocks in diameter exceeding 1 mm at 1500°C and 0.66 MPa [21]. So, an effective approach is to increase the volume of pores with diameters o1 mm to improve the penetration resistance of carbon blocks [22,23]. In the experiment ASC specimens possessed microporous structure with mean pore diameter of 0.2 mm and o1 mm pore volume of up to 80%.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in blast furnace molten metal could easily penetrate into pores of carbon blocks in diameter exceeding 1 mm at 1500°C and 0.66 MPa [21]. So, an effective approach is to increase the volume of pores with diameters o1 mm to improve the penetration resistance of carbon blocks [22,23]. In the experiment ASC specimens possessed microporous structure with mean pore diameter of 0.2 mm and o1 mm pore volume of up to 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Das cinco formas alotrópicas atualmente conhecidas para o elemento carbono, a estrutura de lâminas hexagonais empilhadas que caracteriza o grafi te é a mais desejável para participar da constituição dos materiais refratários. Muito além da sua elevada resistência à temperatura (começaria a sublimar a partir de ≈3700 °C, sendo fusível apenas sob altas pressões [7]), o grafi te apresenta outras importantes características e propriedades que permitem a ele benefi ciar o desempenho desses materiais em diversos aspectos: um baixo coefi ciente de expansão térmica que, combinado com sua elevada condutividade térmica e com a fl exibilidade de sua estrutura cristalina, pode proporcionar ao refratário uma grande resistência às solicitações de choque térmico [8][9][10]; a maior condutividade térmica que ele confere ao refratário também pode levar à formação de uma camada de metal viscosa, ou até mesmo solidifi cada, sobre a face quente do revestimento, o que o protegeria da degradação [11]; suas boas propriedades mecânicas tanto a baixas como a altas temperaturas [9]; a compressibilidade de sua estrutura na direção perpendicular aos planos de grafenos, o que permite que ele absorva a expansão de outros materiais ao seu redor, como a dos agregados de óxidos presentes na composição do refratário [8,9]; e sua reduzida energia superfi cial, que o torna não-molhável por uma grande variedade de líquidos, no que se incluem os óxidos fundidos que compõem as escórias siderúrgicas e a maioria dos metais não-ferrosos e suas ligas. Essa baixa molhabilidade confere ao refratário uma maior resistência química ao ataque desses agentes, mesmo a temperaturas elevadas [8,9].…”
Section: O Carbono E Suas Fontes Para O Refratáriounclassified
“…[ Figure 1: HRTEM images and diffraction patterns from (a) sucrose and (b) anthracite samples, both treated at 1000 °C [13].] grafi te microcristalino podem ser analisadas pelo trabalho de Chen et al [11], no qual se avalia o desempenho de três composições de refratários de alto teor de carbono compostas por diferentes agregados carbonáceos. Em todas elas, o teor desses agregados foi mantido em 66%p da fração sólida total, sendo os 34%p restantes constituídos por teores fi xos de alumina, "fl akes" de grafi te e silício metálico em pó.…”
Section: Fontes De Carbono Particuladasunclassified
See 1 more Smart Citation
“…The first route is adding silicon, and the second is decreasing the size of the filler grains. [6,7] In our previous work, it has been observed that the addition of appropriate silicon content along with its particle size, [8][9][10] activated alumina micropowder, [11] electric-calcined anthracite aggregates, [12] and aluminum [13] can be favorable for the formation of an excellent microporous structure. Also, two routes are proposed toward increasing TC: adding a component with high thermal conductivity and densifying the material.…”
Section: Introductionmentioning
confidence: 99%